Bibliometric Review of Route Optimization in Maritime Transportation: Environmental Sustainability and Operational Efficiency. Issue 6 (June 2023) - Mollaoglu, Mahmut; Altay, Burak Can; Balin, Abit
Route optimization in maritime transportation provides enormous cost saving and efficient resource allocation for companies. Shipping companies need to create an optimized route for shipping fleets. That is why route optimization has gained considerable and increasing attention in maritime transportation literature over the past few years. This research aims to identify the theoretical cornerstones, current research trends, and possible research avenues for future studies by reviewing 256 peer-reviewed route optimization articles in maritime transportation literature. For this purpose, first, theoretical cornerstones of route optimization in maritime transportation literature were examined by co-citation analysis and three clusters were identified: fleet routing and deployment; liner shipping rotation; and optimization of fuel consumption and vessel speeds. Second, current research trends of route optimization in maritime transportation literature were uncovered via bibliographic coupling analysis. The analysis results revealed that current research trends could be considered in four clusters: route planning; routing under different weather conditions; liner shipping network and service design; and environmental speed optimization. Finally, author-keyword analysis was performed to specify knowledge gaps and recommend future research areas.